PENGARUH LINGKUNGAN KERJA DAN FAKTOR MANUSIA TERHADAP TINGKAT KECELAKAAN KERJA KARYAWAN PADA PT. PUTRI MIDAI BANGKINANG KABUPATEN KAMPAR - Dewi Transiska; Nuryanti '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at PT. PutriMidai Kampar district, with the aim to determine the effect of the Working Environment and Human Factor either simultantaneously or partially on Occupational Accidents employees at PT. PutriMidai Kampar District. Population of 112 persons and the number of samples is as many as 52 people. Which is based on the method of slovin. As an independent variable is this study is the Working Environment and Human Factors and the dependent variable is the accident While the data analysis techniques using multiple linear regression with thwhwlp of SPSS (Statistical Package for Social Science ) Version 18. Based on the results of the F test is known that the Working Environment and Human Factors simultaneously significant effect on Work Accidents employees. While based on the results of the t test is known that the Working Environment and Human Factors partially significant effect on accidents of employees at PT. PutriMidai Kampar District. Based on the test results obtained by the value of the coefficient of determination R square in research, then this value will be changed to the shape percent. This means that the percentage contribution of variables influene the Work Environment and Human Factor on Employees’ Accident at PT. PutriMidai Kampar district as much as 62.3%, while the remaining 37.7% influenced by variables not examined in this study. Recommendation that researchers can ask for the company so that the company can make some improvesments to the aspects of the accident. Due to achieve the objectives of the company itself is a way to prevent accidents at work.Keywords : Accident, Environment And Human Factors